Sharing is easy, right? - Stockholm University services for research data and the conundrum of sharing - Tuija Drake af Hagelsrum; Sofie Wennström (Stockholm University, 2017)
This is the slides and the speaking manuscript of a presentation given
at the event Figshare fest in Amsterdam, Netherlands on June 28th 2017. The
presentation is meant to show a case study of organizing research data management in a university both from the management and user perspectives.
The presentation
describes how the Stockholm University Library team is currently (June 2017) working to manage
research data at Stockholm University across different administrative departments. The presentation also includes an
overview of the current research data management activities at the Stockholm University with a deeper insight on working with a knowledge hub for research data management based on user feedback.
Keywords: 80706 Librarianship; Information Studies; Biblioteks- och informationsvetenskap